The Effect of Teaching English Vocabulary on Junior High School Students By Using Wordwall.net - Friza Shabrina; Wahyu Taufiq (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
The use of web in the teaching and learning process is one of the fun and challenging learning innovations such as wordwall.net. With this web students can memorize and remember vocabulary with interesting games. Wordwall.net offers a variety of interesting and original vocabulary-building games. The researchers discovered a problem through interview with a teacher: student scores are still low in one area of the assessment, so the purpose of this research was to investigate the impact of using wordwall.net on students’ English vocabulary in SMP Negeri 1 Wonoayu. This research used a true-experimental design with 35 students in the experimental group and 35 students in the control group. A vocabulary test was one of the research tools utilized in this study to gather data. The treatment was carried out for 3 weeks. The data analysis results revealed that there was difference between mean score of pre-test and post-test in both groups. The pre-test mean score was 65.00 (experimental group) and 57.73 (control group) and the post-test average score was 89.13 (experimental group) and 77.90 (control group). With SPSS version 26, an independent sample t-test was used to analyze the data. The result showed that the probability value of both groups is 0.001, so it indicates that wordwall influences students’ vocabulary improvement. Therefore, it might be suggested that applying Wordwall.net was beneficial in increasing students' vocabulary knowledge.